Regulating Self-Image on Instagram: Links Between Social Anxiety, Instagram Contingent Self-Worth, and Content Control Behaviors - Lopez, Richard B.; Polletta, Isabel (Frontiers in Psychology, 2021)
Social media platforms have provided human beings with unprecedented ways to virtually connect with one another, creating a novel and complex arena for psychological research. Indeed, a growing body of research has uncovered links between social media use and various aspects of health and wellbeing. However, relatively little work has examined factors that characterize how people experience and regulate their online selves on particular platforms. In the present study, we recruited a large sample of active Instagram users (N=247; ages 18-58) to complete a questionnaire battery that included measures of participants’ social anxiety, their sense of self-worth tied to Instagram use, and specific content control behaviors on the Instagram platform (e.g., editing captions, disabling comments, etc.). Results indicated that participants with higher levels of social anxiety tended to have greater Instagram contingent self-worth, and this was then associated with some content control behaviors, including editing captions and photos and videos when sharing posts. These findings suggest that those who are more socially anxious interact with Instagram differently, and this may arise from self-worth that is wedded to their experiences on the platform. Overall, this work adds to a growing body of research highlighting the benefits and risks of social media use on psychological health.